TINDAKAN MEMINTA DALAM NOVEL OLIVER TWIST KARYA CHARLES DICKENS : SUATU ANALISIS PRAGMATIK - RUMAGIT, MARIO VICINI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This research entitled â€œTindakan Meminta dalam Novel Oliver Twist Karya Charles Dickens: Suatu Analisis Pragmatikâ€ is focused on the one kinds of illocutionary act that is acts of requesting. The purpose of this research, is to identify, classify, analyze, and describe the aspect of act of requesting in the novel â€œOliver Twistâ€ by Charles Dickens, and is done by using descriptive method. In collecting data, the writer concentrated on the utterances which contain the act of requesting produced by the characters in novel. The collected data are analyzed based on Austinâ€™s theory. The result shows that there are nine types of acts of requesting in the novel Oliver Twist, they are: ask, beg, command, demand, direct, inquire, order, pray, and request. It is expected that this research will help the students and the other readers in learning the pragmatics aspects, especially about illocutionary act. Keyword: Act ofÂ  Requesting, Illocutionary act, Pragmatics, Novel Oliver Twist.